Taking acute medical imaging to the patient, the domiciliary based X-ray response team. Issue 2 (May 2022) - Mark, S.; Henderson, D.; Brealey, J.
Abstract: Objectives: In 2019 NHS England and NHS Improvement announced their strategy to safely reduce the number of patients who are unnecessarily conveyed into a hospital setting by 2023. The recent coronavirus pandemic emphasised the importance of reducing avoidable conveyance. Consequently, a multidisciplinary team consisting of a Paramedic, Radiographer and Emergency Care Clinician was created to respond to Category 3 and 4 calls to assess patients in their own home using an array of specialised diagnostic equipment including a lightweight portable X-ray unit supplied by Fujifilm, the FDR Xair. This team was named the X-ray response team (XRT). Key findings: Over a 7-month period the team attended 54 calls, the majority of which were in the patient's private residence (86%), the overall average age of the patients attended was 80 years. A patient survey found 100% of respondents rated the service as very good with 100% also feeling that they were treated with respect and dignity. The team reduced avoidable conveyance by 50% as 27 of the 54 patients were discharged on scene and kept at home. Conclusion: Proof of concept was achieved. The XRT improved patient care and experience as patients were assessed and diagnosed in their home environment which also minimised the risk of contracting hospital acquired infections. Implications for practice: The XRT reduced avoidable conveyance by 50% with 100% of the patient's involved providing positive feedback. The team are exploring new pathways that would allow direct referral to specialist teams in the hospital such as care of the elderly and orthopaedics which would: improve patient experience, ease A&E pressures, reduce costs and make the most effective use of the resources available.